Expansion of CD4+CD8+ double-positive T cells in rheumatoid arthritis patients is associated with erosive disease. (14th July 2021) - Nguyen, Phuong; Melzer, Marc; Beck, Felix; Krasselt, Marco; Seifert, Olga; Pierer, Matthias; Rothe, Kathrin; Wagner, Ulf
Abstract: Objectives: CD4 + CD8 + double-positive (DP) T cells are expanded in the peripheral blood of a subset of patients with RA. This study examines the clinical significance of DP T cells in RA. Methods: In 70 RA patients, DP T cells were measured by flow cytometry. Clinical data were obtained, and hand and feet radiographs were scored according to the Sharp/van der Heijde (SvdH) method. The association between DP T cell frequency and erosive joint destruction was analysed by correlation and multiple logistic regression analysis. Results: Nineteen RA patients (27.1%) displayed increased DP T cell frequencies, which correlated with age ( r  = 0.288, P =0.016). Expansion of DP T cells was associated with the occurrence of erosions (94, 7% vs 43, 1%, P <0.001), with a higher SvdH joint damage score (24.5 vs 6, P =0.008) and with more frequent use of biologic or targeted-synthetic DMARDs (68.4% vs 38%, P =0.02). In patients with non-erosive disease, DP T cell frequencies correlated with the joint space narrowing score ( n  = 28, r  = 0.44, P =0.02). Logistic regression revealed DP T cells to be associated with erosive disease (OR 1.90, P <0.05). Conclusion: Expansion of DP T cells is associated with joint damage and frequent escalation of therapy, possibly suggesting a contribution to more severe RA.